(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
A high recovery rate after one course of treatment and a relatively low relapse rate (associated with a change in sexual partner or the presence of a urogenital tract infection) make this drug recommended for the treatment of cervicitis.